A Provably Secure Revocable ID-Based Authenticated Group Key Exchange Protocol with Identifying Malicious Participants. (1st June 2014) - Wu, Tsu-Yang; Tsai, Tung-Tso; Tseng, Yuh-Min
Abstract : The existence of malicious participants is a major threat for authenticated group key exchange (AGKE) protocols. Typically, there are two detecting ways (passive and active) to resist malicious participants in AGKE protocols. In 2012, the revocable identity- (ID-) based public key system (R-IDPKS) was proposed to solve the revocation problem in the ID-based public key system (IDPKS). Afterwards, based on the R-IDPKS, Wu et al. proposed a revocable ID-based AGKE (RID-AGKE) protocol, which adopted a passive detecting way to resist malicious participants. However, it needs three rounds and cannot identify malicious participants. In this paper, we fuse a noninteractive confirmed computation technique to propose the first two-round RID-AGKE protocol with identifying malicious participants, which is an active detecting way. We demonstrate that our protocol is a provably secure AGKE protocol with forward secrecy and can identify malicious participants. When compared with the recently proposed ID/RID-AGKE protocols, our protocol possesses better performance and more robust security properties.